Take super capacitor's fuel cell electric automobile power device - LU YUZHENG; LI JUNJIAO; DONG YIWANG (2016)
The utility model discloses a take super capacitor's fuel cell electric automobile power device mainly includes automatically controlled unit, power converter, detecting element, driving motor, derailleur, drive wheel, differential mechanism, fuel holding vessel, separator, electrical control valve, fuel cell stack, ultracapacitor system. When electric automobile accelerateed, super capacitor supplied power for driving motor, during the electric automobile braking, the driving motor operation is filled among the ultracapacitor system at rectification mode, the electric energy that the braking produced in generating mode, power converter operation. When electric automobile normally travel, the driving motor operation moved in the contravariant mode at electric mode, power converter, and fuel cell stack supplies power for driving motor. When electric automobile gave it the gun, the driving motor operation moved in the contravariant mode at electric mode, power converter, and ultracapacitor system supplies power